Severe Acute Respiratory Syndrome Coronavirus 2 RNAemia and Clinical Outcomes in Children With Coronavirus Disease 2019. (7th October 2021) - Mertz, Cameron; Glowinski, Rebecca; Cohen, Shira H; Mertz, Sara; Ye, Fang; Hall, Mark W; Peeples, Mark E; King, Tiffany; Wang, Huanyu; Leber, Amy L; Sanchez, Pablo J; Ramilo, Octavio; et al.
Abstract: The burden of coronavirus disease 2019 (COVID-19) in children represents a fraction of cases worldwide, yet a subset of those infected are at risk for severe disease. We measured plasma severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in a cohort of 103 children hospitalized with COVID-19 with diverse clinical manifestations. SARS-CoV-2 RNAemia was detected in 27 (26%) of these children, lasted for a median of 6 (interquartile range, 2–9) days, and was associated with higher rates of oxygen administration, admission to the intensive care unit, and longer hospitalization. Abstract : In a cohort of 103 children and adolescents hospitalized with COVID-19 with diverse clinical manifestations, SARS-CoV-2 RNAemia was detected in 26% of them, lasted for 6 (interquartile range, 2–9) days, and was associated with worse clinical outcomes.